Highlights of the finalization meeting of the joint innovative project on in-service primary teacher education held on 3-12 December 1981, New Delhi, India. (Education quarterly.)
The meeting was attended by 25 participants from nine countries: three from Bangladesh, Indonesia, Malaysia, the Philippines, Republic of Korea and Thailand; four from India; one from Maldives; and two from Nepal. In-depth study and discussion focused on three major areas: (a) development of guidelines for research and evaluation, (b) development of guidelines for further refinement of alternative schemes/implementation strategies, and (c) suggestions for national follow-up action. All evaluation efforts have one common aim, the improvement of the programme. It is only the knowledge of evaluation findings that will help planners, organizers, resource persons and user agencies as well as clients to improve the organization in in-service primary teacher education programme.